Impact of antibiotic timing on mortality from Gram-negative bacteraemia in an English district general hospital: the importance of getting it right every time. (21st November 2020) - Baltas, Ioannis; Stockdale, Thomas; Tausan, Matija; Kashif, Areeba; Anwar, Javeria; Anvar, Junaid; Koutoumanou, Eirini; Sidebottom, David; Garcia-Arias, Veronica; Wright, Melanie; Democratis, Jane
Abstract: Objectives: There is limited evidence that empirical antimicrobials affect patient-oriented outcomes in Gram-negative bacteraemia. We aimed to establish the impact of effective antibiotics at four consecutive timepoints on 30 day all-cause mortality and length of stay in hospital. Methods: We performed a multivariable survival analysis on 789 patients with Escherichia coli, Klebsiella spp. and Pseudomonas aeruginosa bacteraemias. Antibiotic choices at the time of the blood culture (BC), the time of medical clerking and 24 and 48 h post-BC were reviewed. Results: Patients that received ineffective empirical antibiotics at the time of the BC had higher risk of mortality before 30 days (HR = 1.68, 95% CI = 1.19–2.38, P = 0.004). Mortality was higher if an ineffective antimicrobial was continued by the clerking doctor (HR = 2.73, 95% CI = 1.58–4.73, P < 0.001) or at 24 h from the BC (HR = 1.83, 95% CI = 1.05–3.20, P = 0.033) when compared with patients who received effective therapy throughout. Hospital-onset infections, 'high inoculum' infections and elevated C-reactive protein, lactate and Charlson comorbidity index were independent predictors of mortality. Effective initial antibiotics did not statistically significantly reduce length of stay in hospital (−2.98 days, 95% CI = −6.08–0.11, P = 0.058). The primary reasons for incorrect treatment were in vitro antimicrobial resistance (48.6%), initial misdiagnosis of infection source (22.7%) and non-adherence to hospital guidelines (15.7%). Conclusions: Consecutive prescribing decisions affect mortality from Gram-negative bacteraemia.